A crosstalk free routing algorithm of Generalized Recursive Non-blocking Network - Sultana, Most. Arjuman; Chowdhury, Gita; Rahman, M.M. Hafizur (2008)
Crosstalk is an intrinsic drawback of an optical network, and avoiding crosstalk is important for making fruitful application of optical switching network. In this paper, we apply the well-known semi-permutation technique on generalized recursive network (GRN) to make it crosstalk free. GRN has reasonable path independent signal loss and crosstalk. Using the methodology presented in this paper, that reasonable crosstalk is avoided. For the GRN network, we show that any semi-permutation is realizable in one pass and any permutation is realizable in two passes under the constraint of avoiding crosstalk.